Oximas como inibidores da oxidação de lipoproteínas de baixa densidade - Portella, Rafael de Lima (2009)
The oxidation of low density lipoprotein is now an established hypothesis of atherogenesis and suggests that accumulation of oxidized low density lipoprotein (oxLDL) in the vessel wall is an early event in disease progression. OxLDL represents a variety of modification of both lipid and apolipoprotein B (apoB) components by peroxidation. This promotes atherosclerosis through inflammatory and immunologic mechanisms that lead to the formation of macrophage foam cells. There are studies showing that different antioxidants inhibit both ex vivo LDL oxidation and atherosclerosis in experimental animals. In view of this, we have evaluated the antioxidant properties of the new oximes butane-2,3-dionethiosemicarbazone and 3-(phenylhydrazono)butan-2-one against Cu2+-induced LDL and serum oxidation. Conjugated dienes formation, loss of tryptophan fluorescence, and TBARS formation were assassed as oxidation parameters. The results obtained in this study showed that both oximes are able to prevent Cu2+-induced LDL and serum oxidation in a concentration-dependent manner. Moreover, both oximes caused a significant increase in lag phase of conjugated dienes formation and a significant decrease in TBARS production. Indeed, oximes protected the early stage of LDL oxidation as destruction of tryptophan residues of ApoB and the subsequent propagation phase. Oxime butane-2,3-dionethiosemicarbazone showed to be more effective than 3-(phenylhydrazono) butan-2-one in all parameters analyzed. In conclusion, both oximes exhibited a protective role in LDL and serum oxidation. This protection may contribute to prevent LDL oxidation in vivo and thus the atherogenesis. However, further stydies are needed to clarify the oximes antioxidant properties angainst other models of free radical generators and the molecular mechanism in which oximes prevent LDL oxidation.